2002
DOI: 10.1007/s00453-001-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiprocessor Scheduling with Machine Allotment and Parallelism Constraints

Abstract: Abstract. Modern computer systems distribute computation among several machines to speed up the execution of programs. Yet, setup and communication costs, as well as parallelism constraints, bound the number of machines that can share the execution of a given application, and the number of machines by which it can be processed simultaneously. We study the resulting scheduling problem, stated as follows. Given a set of n jobs and m uniform machines, assign the jobs to the machines subject to parallelism and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Beier et al (2004) showed that it is NP-hard to decide whether a PSNE exists within such settings. In addition, Shachnai and Tamir (2002); Krysta et al (2003) obtained similar results for k-splittable congestion games in the job scheduling domain.…”
Section: Related Workmentioning
confidence: 57%
“…Beier et al (2004) showed that it is NP-hard to decide whether a PSNE exists within such settings. In addition, Shachnai and Tamir (2002); Krysta et al (2003) obtained similar results for k-splittable congestion games in the job scheduling domain.…”
Section: Related Workmentioning
confidence: 57%
“…The authors prove that this problem does not admit a PTAS, and provide a dual PTAS and an asymptotic PTAS. In a multiprocessor scheduling context, another related problem is scheduling with allotment and parallelism constraints [26]. The goal is to schedule a certain number of tasks, where each task comes with a bound on the number of machines that can process it simultaneously and a bound on the overall number of machines that can participate in its execution.…”
Section: Related Workmentioning
confidence: 99%
“…This problem can also be seen as a splittable packing problem, but this time with a bound k i on the number of times an item can be split. In [26], an approximation algorithm of ratio…”
Section: Related Workmentioning
confidence: 99%
“…All the proofs of upper bounds use only these bounds on OPT, and therefore the knowledge of the actual values of OPT is not required. Naturally, those bounds are not always tight as the offline problem is NP-complete already for identical machines and any constant [19]. Note that in almost all cases in this paper where we got tight bounds on the competitive ratio, the value of OPT is actually given by the maximum of the two bounds on OPT.…”
Section: Computing Optmentioning
confidence: 98%
“…Previous work: The basic model (with = s = 1) was studied in a sequence of papers, each improving either the upper bound or the lower bound on the competitive ratio [10,7,2,12,1,9,6,11]. The offline splittable jobs problem was studied by Shachnai and Tamir [19]. They showed that the problem is NP-hard (already for identical machines) and gave a PTAS for uniformly related machines.…”
Section: Introductionmentioning
confidence: 99%